For question 6

Make x for first one subject of formulae

then it becomes

x=-2y

Substitution means replace your answer in the second part

since x=-2y

3(-2y) +4y = 4

-6y+4y=4

-2y=4

y= 4/-2

y=-2

Now to find x,replace the answer for y in one in the equation

so i replace y=-2 in the first part

x=-2y

x= -2(-2)

x=4

Therefore x=4 and y=-2

To check your answer replace x and y by the values you got and check if you get same answer.

$12,500 loan will come as $19,250 after 3 years

Sin (α ^ 2) + cos (α ^ 2) = 1

False

To solve the problem let's make the following change of variables:

x = α ^ 2

We substitute in the original equation:

Sin (x) + cos (x) = 1

We observe that the trigonometric equation is false.

The trigonometric identity that is equal to one is the sum of the sine to the square of an angle plus the cosine to the square of the same angle. In other words, mathematically it is written as:

(Sin (α)) ^ 2 + (cos (α)) ^ 2 = 1

**answer**

** false**

**Answer:**

2x-3

**Step-by-step explanation:**